The Covid-19 Pandemic Impact On Learning Students SD Sangubanyu 1 - Kharisma Amar Fauzi; Aura Zayinatul Fitria; Ika Priharyani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Covid-19 is a major obstacle to Indonesian society especially in the field of education. Sogovernments introduced an online learning system to prevent the spread of the covid-19virus. But in implementing that system there are still many flaws that are found inparticular the role of parents in helping students understand the material presented bytheir teachers. Parents are engaged to understand the technological development that is amajor prerequisite for online study. The purpose of this study is to know how importantthe role of parents is to the learning result of learners. The study employed a method ofobservation involving several apprentices from Sangubanyu 1's primary school in thestudy. The result of the study is that the value of students is consistent with theparticipation of parents in the work or testing given by their teachers. So it cannot bedenied that a student's grades are becoming better than they used to be.